Indications, Complications, and Outcomes of Cardiac Surgery After Heart Transplantation: Results From the Cash Study - Gökler, Johannes; Aliabadi-Zuckermann, Arezu Z.; Kaider, Alexandra; Ambardekar, Amrut V.; Antretter, Herwig; Artemiou, Panagiotis; Bertolotti, Alejandro M.; Boeken, Udo; Brossa, Vicens; Copeland, Hannah; Generosa Crespo-Leiro, Maria; Eixerés-Esteve, Andrea; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Allograft pathologies, such as valvular, coronary artery, or aortic disease, may occur early and late after cardiac transplantation. Cardiac surgery after heart transplantation (CASH) may be an option to improve quality of life and allograft function and prolong survival. Experience with CASH, however, has been limited to single-center reports. Methods We performed a retrospective, multicenter study of heart transplant recipients with CASH between January 1984 and December 2020. In this study, 60 high-volume cardiac transplant centers were invited to participate. Results Data were available from 19 centers in North America (n = 7), South America (n = 1), and Europe (n = 11), with a total of 110 patients. A median of 3 (IQR 2–8.5) operations was reported by each center; five centers included ≥ 10 patients. Indications for CASH were valvular disease (n = 62), coronary artery disease (CAD) (n = 16), constrictive pericarditis (n = 17), aortic pathology (n = 13), and myxoma (n = 2). The median age at CASH was 57.7 (47.8–63.1) years, with a median time from transplant to CASH of 4.4 (1–9.6) years. Reoperation within the first year after transplantation was performed in 24.5%. In-hospital mortality was 9.1% (n = 10). 1-year survival was 86.2% and median follow-up was 8.2 (3.8–14.6) years. The most frequent perioperative complications were acute kidney injury and bleeding revision in 18 and 9.1%, respectively. Conclusion Cardiac surgery after heart transplantation has low in-hospital mortality and postoperative complications in carefully selected patients. The incidence and type of CASH vary between international centers. Risk factors for the worse outcome are higher European System for Cardiac Operative Risk Evaluation (EuroSCORE II) and postoperative renal failure.